2015
DOI: 10.1007/s00281-015-0480-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of CD8 T lymphocytes in rickettsial infections

Abstract: Arthropod-borne obligately intracellular bacteria pose a difficult challenge to the immune system. The genera Rickettsia, Orientia, Ehrlichia, and Anaplasma evolved mechanisms of immune evasion, and each interacts differently with the immune system. The roles of CD8 T cells include protective immunity and immunopathology. In Rickettsia infections, CD8 T cells are protective mediated in part by cytotoxicity toward infected cells. In contrast, TNFα overproduction by CD8 T cells is pathogenic in lethal ehrlichios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 97 publications
(111 reference statements)
2
28
0
2
Order By: Relevance
“…It is close to the prevalences reported by Brown et al [69] in free-roaming dogs associated with remote Aboriginal communities in Australia, but higher than other studies carried out in Brazil [62], Ivory Coast [70], Kenya [70] and Uganda [59]. The higher probability of A. platys infections in young dogs in our study was already been recorded in a previous study in Africa [70], most likely due to a primary exposure of juvenile individuals to the pathogen [71,72] and might be related to the lower levels CD8 T lymphocytes found in young dogs [73], which has a role in clearance of rickettsial infections [74]. In agreement with our results, other studies found that dogs infested with R. sanguineus were more likely to be infected with or exposed to Anaplasma spp.…”
Section: Discussionsupporting
confidence: 47%
“…It is close to the prevalences reported by Brown et al [69] in free-roaming dogs associated with remote Aboriginal communities in Australia, but higher than other studies carried out in Brazil [62], Ivory Coast [70], Kenya [70] and Uganda [59]. The higher probability of A. platys infections in young dogs in our study was already been recorded in a previous study in Africa [70], most likely due to a primary exposure of juvenile individuals to the pathogen [71,72] and might be related to the lower levels CD8 T lymphocytes found in young dogs [73], which has a role in clearance of rickettsial infections [74]. In agreement with our results, other studies found that dogs infested with R. sanguineus were more likely to be infected with or exposed to Anaplasma spp.…”
Section: Discussionsupporting
confidence: 47%
“…If the cellular tropism of R . typhi and the associated cytotoxic T cell responses providing protective immunity in part by cytotoxicity towards infected cells contribute to nucleosome release remains to be determined [ 8 , 46 ]. However, in scrub typhus the data point towards neutrophils as a potential source of nucleosomes, contributing to disease exacerbation reflected by association to clinical disease severity ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…tsutsugamushi infected monocyte-derived dendritic cells induce production of IFN-γ from CD4+ T-cells [ 17 ]. Scrub typhus is universally fatal in CD8-deficient mice (compared to 50% fatality in wild type mice) [ 18 ], and CD8+ T-cells play a vital protective role in control of O . tsutsugamushi growth [ 19 ].…”
Section: Introductionmentioning
confidence: 99%